Effects of indoor summer dehumidification and winter humidification on the physiological and subjective responses of the elderly. (January 2023) - Hashiguchi, Nobuko; Tochihara, Yutaka; Takeda, Akira; Yasuyama, Yukari
Abstract: The purpose of this study was to clarify the physiological and subjective responses of the elderly to dehumidification in a humid summer and humidification in a dry winter compared with the young. Sixteen elderly and sixteen young subjects participated in the dehumidification experiment (DE) and 13 elderly and 15 young subjects participated in the humidification experiment (HE). The air temperature in the climate chamber was set at 28 °C, and humidity was decreased from 70% relative humidity (RH) to 50% RH for 90 min in the DE. The air temperature was set at 25 °C, and the humidity was increased from 30% RH to 50% RH for 90 min in the HE. Skin temperature, body weight, transepidermal water loss (TEWL), skin hydration state, saccharin clearance time (SCT), and blinking frequency were measured during exposure; whereby we evaluated humidity sensation, thermal sensation, and thermal comfort. Dehumidification caused a significant decrease in skin temperature in both age groups owing to greater insensible perspiration. Humidification significantly shortened the SCT in both age groups. TEWL increased significantly in the DE and decreased in the HE. For the physiological responses (skin temperature, skin physiology, SCT, and blinking frequency) to dehumidification and humidification, no distinct differences between the age groups were observed. However, subjective responses suggested that the elderly were less sensitive to humidity differences than the young in both the DE and HE. Highlights: Dehumidification decreases skin temperature because of insensible perspiration. Humidification is effective in maintaining the nasal mucosa function. Dehumidification increases and humidification decreases transepidermal water loss. Physiological responses to dehumidification and humidification are not age-related. Elderly are generally less sensitive to changes in humidity compared to young.